Hedging Foreign Exchange Risk in Chile : Markets and Instruments - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 2005)
Policy makers have expressed interest in fostering the development of local foreign exchange derivatives markets with a view to reducing risks arising from currency mismatches between assets and liabilities in the corporate sector. This paper assesses foreign exchange exposure in the corporate sector in Chile, analyzes the current state of the foreign exchange derivatives market in Chile, and argues that liquid and developed foreign exchange derivatives markets can help promote financial stability.